2014
DOI: 10.3389/fpls.2014.00539
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene, a key factor in the regulation of seed dormancy

Abstract: Ethylene is an important component of the gaseous environment, and regulates numerous plant developmental processes including seed germination and seedling establishment. Dormancy, the inability to germinate in apparently favorable conditions, has been demonstrated to be regulated by the hormonal balance between abscisic acid (ABA) and gibberellins (GAs). Ethylene plays a key role in dormancy release in numerous species, the effective concentrations allowing the germination of dormant seeds ranging between 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
237
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(253 citation statements)
references
References 178 publications
(294 reference statements)
6
237
0
10
Order By: Relevance
“…ROS signaling has been reported to cross-talk with plant hormone ethylene during germination of seeds and pollen (46). In this study, we found the abundances of six proteoforms of two ethylene biosynthesis-related enzymes (SAMS and MetS) were changed, four of which were reduced but two were induced during spore germination (Table I, Fig.…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 60%
See 1 more Smart Citation
“…ROS signaling has been reported to cross-talk with plant hormone ethylene during germination of seeds and pollen (46). In this study, we found the abundances of six proteoforms of two ethylene biosynthesis-related enzymes (SAMS and MetS) were changed, four of which were reduced but two were induced during spore germination (Table I, Fig.…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 60%
“…However, early studies have reported that exogenous ethylene partially inhibited the spore germination of fern species C. richardii (51) and O. sensibilis (52). The critical stage of spore germination inhibited by ethylene is prior to nuclear migration and cell division (52), whereas the ethylene inhibition of cell division is attributed to the inhibition of chromatin activity, DNA synthesis, and chromosome replication (46,53). This implies that exogenous ethylene treatment subsequent to DCSs stage was ineffective in blocking the germination of O. sensibilis spores (52).…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 99%
“…1754) [67]. Grafting experiments with ABA-deficient mutants of tomato showed that stomata can close independently of the leaf water status, suggesting that there is a chemical signal produced by the roots that controls stomata conductance [68]. Therefore, the selection of rootstocks with adequate biosynthesis and perception of the ABA could improve the efficient use of water and the drought tolerance of many horticultural varieties.…”
Section: Grafting As An Agronomic Tool To Improve Drought Tolerancementioning
confidence: 99%
“…temperatura, luz, entre otras) y, a nivel endógeno, por hormonas vegetales, como giberelinas, ácido abscísico y etileno. Las giberelinas y el etileno están involucrados en la inducción de la germinación y la ruptura de latencia de numerosas especies (Peng & Harberd, 2002;Corbineau, Xia, Bailly, & El-Maarouf-Bouteau, 2014). La aplicación exógena de giberelinas y/o etileno estimula la germinación de semillas sin latencia, incubadas bajo condiciones no óptimas, y también rompe la latencia primaria (Finch-Savage & Leubner-Metzger, 2006;Corbineau et al, 2014).…”
unclassified
“…Las giberelinas y el etileno están involucrados en la inducción de la germinación y la ruptura de latencia de numerosas especies (Peng & Harberd, 2002;Corbineau, Xia, Bailly, & El-Maarouf-Bouteau, 2014). La aplicación exógena de giberelinas y/o etileno estimula la germinación de semillas sin latencia, incubadas bajo condiciones no óptimas, y también rompe la latencia primaria (Finch-Savage & Leubner-Metzger, 2006;Corbineau et al, 2014). Giberelinas y etileno interactúan en la ruptura de la latencia de semillas, sugiriéndose que el etileno aumenta la producción y sensibilidad a giberelina, lo cual estimula la germinación (Corbineau et al, 2014).…”
unclassified